Translation and cross-cultural adaptation of the Cardiff Wound Impact Schedule to Brazilian Portuguese - Augusto, Fabiana da Silva; Blanes, Leila; Nicodemo, Denise [UNESP]; Ferreira, Lydia Masako (Elsevier, 2017)
Aim To translate into Brazilian Portuguese and cross-culturally adapt the Cardiff Wound Impact Schedule, a specific measure of health-related quality of life (HRQoL) for patients with chronic wounds. Chronic wounds have a relevant impact on the HRQoL of patients. However, there are few instruments cross-culturally adapted and validated in Brazil to assess HRQoL in patients with wounds. Methods A descriptive cross-sectional study was conducted following six steps: (1) translation of the original instrument into Brazilian-Portuguese by two independent translators; (2) construction of a consensus version based on both translations; (3) two independent back-translations into English of the consensus version; (4) review by an expert committee and construction of the pre-final version; (5) testing of the pre-final version on patients with chronic wounds; and (6) construction of the final version. The psychometric properties of the instrument were tested on 30 patients with chronic wounds of the lower limb; 76.7% were men, 70.0% had traumatic wounds, and 43.3% had the wound for more than 1 year. Participants were recruited from an outpatient wound care clinic in São Paulo, Brazil. Results The final version approved by the expert committee was well understood by all patients who participate in the study and had satisfactory face validity, content validity, and internal consistency, with Cronbach's alpha coefficients ranging from 0.681 to 0.920. Conclusion The cross-culturally adapted Brazilian-Portuguese version of the instrument showed satisfactory face and content validity, good internal consistency, and was named Cardiff Wound Impact Schedule-Federal University of São Paulo School of Medicine or CWIS-UNIFESP/EPM.
Keywords: Evaluation; Quality of life; Reproducibility of results; Validation studies; Wounds and injuries